Al-Madih Poetry as An Instrument of Power Legitimization in The Umayyad Era - Ardiansyah, Rafli; Sakinah, R. Myrna Nur (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the role of al-madih (praise poetry) as an instrument of political legitimization during the Umayyad Dynasty. While al-madih originally functioned as a literary genre for expressing admiration and honoring individuals, it gradually evolved into a political medium that reinforced the authority of the ruling dynasty. This research aims to analyze how praise poetry was employed to construct the public image and legitimacy of Umayyad rulers through the works of three prominent court poets: Al-Akhtal, Jarir, and Al-Farazdaq. Using a qualitative descriptive approach and qualitative content analysis, the study examines selected poems alongside historical and literary sources related to the political and cultural context of the Umayyad period. The findings reveal that al-madih functioned not merely as a form of artistic expression but also as an effective tool of political communication. Through rhetorical devices such as metaphor, hyperbole, symbolism, and genealogical references, these poets portrayed Umayyad caliphs as just, divinely sanctioned, and legitimate rulers while simultaneously strengthening the dynasty’s public image and responding to political opposition. The study concludes that al-madih played a significant role in consolidating Umayyad political authority, demonstrating the close relationship between Arabic literature and political power in early Islamic civilization.